Deficiency of PPARγ in Bone Marrow Stromal Cells Does not Prevent High-Fat Diet-Induced Bone Deterioration in Mice. Issue 9 (10th June 2021) - Cao, Jay J; Gregoire, Brian R; Michelsen, Kim G; Shi, Xingming
ABSTRACT: Background: Bone marrow osteoblasts and adipocytes are derived from a common mesenchymal stem cell and have a reciprocal relationship. Peroxisome proliferator-activated receptor gamma (PPARγ), a regulator for adipocyte differentiation, may be a potential target for reducing obesity and increasing bone mass. Objectives: This study tested the hypothesis that bone-specific Pparg conditional knockout (cKO), via deletion of Pparg from bone marrow stromal cells (BMSC) using Osterix 1 (Osx1)-Cre, would prevent high-fat (HF) diet–induced bone deterioration in mice. Methods: PPARγ cKO (PPARγ fl/fl : Osx1-Cre) and floxed littermate control (PPARγ fl/fl Osx1-Cre – ) mice that were 6 weeks old were randomly assigned to 4 groups ( n  = 12/group, 6 male and 6 female) and fed ad libitum with either a normal-fat (NF) purified diet (3.85 kcal/g; 10% energy as fat) or an HF diet (4.73 kcal/g; 45% energy as fat) for 6 mo. Bone structure, body composition, and serum bone-related cytokines were measured. Data were analyzed by 2-way ANOVA with Tukey post hoc comparison. Results: The HF diet decreased the tibial and lumbar vertebrae trabecular bone volume/total volume (BV/TV) by 28% and 18%, respectively, compared to the NF diet ( P < 0.01). PPARγ cKO mice had 23% lower body fat mass and 9% lower lean mass than control mice. PPARγ cKO mice had 41% greater tibial trabecular BV/TV compared to control mice. None of trabecular bone parameters at the second lumbar vertebra were affected by genotype. PPARγ cKO mice had decreased cortical thickness compared to control mice. PPARγ cKO mice had a 14% lower ( P < 0.01) serum concentration of leptin and a 35% higher ( P < 0.05) concentration of osteocalcin compared with control mice. Conclusions: These data indicate that PPARγ has site-specific impacts on bone structures in mice and that knockout PPARγ in BMSC increased bone mass (BV/TV) in the tibia but not the lumbar vertebrae. PPARγ disruption in BMSC did not prevent HF diet–induced bone deterioration in mice.